Bioenergy from agroforestry can lead to improved food security, climate change, soil quality, and rural development. (August 2016) - Sharma, Navin; Bohra, Babita; Pragya, Namita; Ciannella, Rodrigo; Dobie, Phil; Lehmann, Sarah
Abstract: Well‐designed bioenergy systems can contribute to several objectives, such as mitigating climate change, increasing energy access, and alleviating rural poverty. With adequate technical assistance and land management, farm yields and income can be increased, food security strengthened, carbon sequestration improved, and pressure for land clearing reduced. There are, nonetheless, risks involved on bioenergy production and several initiatives worldwide have failed to achieve proposed positive outcomes. Overreliance on monoculture plantations, negative land‐use change impacts, and use of cereal crops as feedstocks are among the main causes. Agroforestry systems and practices can address most of these risks and thus play an important role in sustainable production of several bioenergy outputs, including efficient solid biomass, biogas, liquid biofuels, and dendro power. This article assesses the potential of such integrated approaches to provide multiple benefits, including the coproduction of food, animal feed, and organic fertilizers, while respecting economic, social, and environmental sustainability indicators. Building on experiences from sub‐Saharan Africa, developing Asia, and Latin America, promising perennial species, production models, and value chains are analyzed. Finally, key challenges and potential solutions for larger scale adoption of integrated food‐energy approaches are also identified and discussed. Abstract : Agroforestry approaches, because of their multiple benefits, are also uniquely placed to address various challenges associated with bioenergy production. This paper highlights the importance of energy for various developmental needs and provides lessons learnt from various agroforestry‐based projects and recommends the way forward.